Recruitment/Selection and Training/Development Practices : Value-Added Contribution towards Organizational Effectiveness  - Abang Ekhsan, Abang Othman (Nicolae Titulescu University, 2009)
Purpose - The purpose of this paper is to examine the applications of key human resource management functions of recruitment/selection and training/development and explore perceptions on their value-added contribution towards organizational effectiveness in the context of two major Japanese owned multinational electronics companies in Malaysia.